THE INNOVATION OF AL-NAJJAR’S THOUGHT IN MAQASID AL-SHARI’AH - Zahwa Syihab (Mimbar Agama Budaya, 2021)
Abstract. This article examines the maqasid al-shari‘ah formulated by al-Najjar, a Tunisian thinker who was born on May 28, 1945, in his work maqasid al-shari‘ah bi Ab’ad Jadidah. This research shows that maqasid al-shari‘ah according to al-Najjar is the purpose (al-ghayah) of the Islamic law’s application at both the universal and particular levels. This definition is in accordance with previous maqasidi thinkers, such as Ibn ‘Asyur and ‘Ilal al-Fasi. The innovation about maqasid al-shari‘ah which was initiated by Al-Najjar lies in the classification of maqasid al-shari‘ah into four main objectives: protecting the value of human life (hifzh qimat al-hayah al-insaniyyah), protecting human essence (hifzh al-dzat al-insaniyyah), protecting society (hifzh al-mujtama’) and protecting the physical environment (hifzh al-muhit al-maddi). Furthermore, al-Najja r also emphasized that all of these purposes originate and lead to the universal purposes of the shari’a (maqasid al-syari ‘ah al-kulliyah). Al-Najjar also tries to make the orientation of maqasid al-shari‘ah from the partial-individual benefit to the universal-social benefit. Abstrak. Artikel ini mengkaji tentang pemikiran maqasid al-shari‘ah yang rumuskan oleh al-Najjar, seorang pemikir asal Tunisia yang lahir pada 28 Mei 1945, dalam karyanya Maqasid al-shari‘ah bi Ab’ad Jadidah. Penelitian ini menunjukkan bahwa maqasid al-shari‘ah menurut al-Najjar adalah tujuan (al-ghayah) diberlakukannya syariat Islam baik pada level universal maupun partikular. Definisi ini sesuai dengan para pemikir maqasidi sebelumnya, seperti Ibn ‘Asyur dan ‘Ilal al-Fasi. Adapun inovasi yang digagas oleh Al-Najjar dalam kajian maqasid al-shari‘ah terletak pada klasifikasi maqasid al-shari‘ah menjadi empat tujuan utama, yaitu melindungi nilai kehidupan manusia (hifzh qimat al-hayah al-insaniyyah), melindungi esensi manusia (hifzh al-dzat al-insaniyyah), menjaga masyarakat (hifzh al-mujtama’) dan menjaga lingkungan fisik (hifzh al-muhit al-maddi). Al-Najjar juga berupaya untuk menjadikan orientasi maqasid al-shari‘ah dari kemaslahatan yang cenderung parsial-individual kepada kemaslahatan universal-sosial.